PENERAPAN TEORI KENDALI PADA MASALAH INVENTORI - Pardi Affandi; Faisal Faisal; Yuni Yulida (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2012)
This paper will examine the application of Control Theory to the problem Inventory, will be developed the first model in which dynamic demand and inventory available all the time. The discussion focused on inventory system analysis nonlinear-shaped production and production costs are treated as a function each inventory level and production level. Then expanded the model first to the next model where the decline in goods is taken into account. Level damage is calculated as a function of time with the amount already available. For both models, optimal control theory will be used to obtain policy optimal control, to obtain optimal results.